Pocket Guide to Echocardiography - Kacharava, Andro G.; Gedevanishvili, Alexander T.; Imnadze, Guram G.; Tsverava, Dimitri M.; Brodsky, Craig M. (Chicester : Wiley, 2012)
With its easy accessibility, low cost, and ability to deliver, essential bedside information about the cardiac structure and function, echocardiography has become one of the most relied-upon diagnostic tools in clinical medicine. As a result, more clinicians than ever before must be able to accurately interpret echocardiographic information in order to administer appropriate treatment. Based on the authors' experience teaching echocardiography in busy clinical settings, this new pocketbook provides reliable guidance on everyday clinical cardiac ultrasound and the interpretation of ech.
25 Normal echocardiographic values for prosthetic valvesProsthetic valves in the aortic position; Prosthetic valves in the mitral position; Annular rings in the mitral position; 26 Congenital heart disease; VSD; ASD; 27 Miscellaneous; 28 Aortic diseases; Aortic atherosclerosis (Katz's classification); 29 Indication for surgery in aortic diseases; The indications for surgery for thoracic aneurysm include; The indications for surgery for abdominal aneurysm include; 30 Transthoracic echocardiographic and Doppler protocols for assessment of ventricular dyssynchrony.
Two methods of diagnosing cardiac intraventricular dyssynchrony with tissue Doppler imaging.
Includes bibliographical references and index.
Print version record.
Keywords: Echocardiography -- Handbooks, manuals, etc; Echocardiography -- methods; Heart Diseases -- ultrasonography; Echocardiography -- methods; Heart Diseases -- ultrasonography; HEALTH & FITNESS -- Diseases -- Heart; MEDICAL -- Cardiology; Echocardiography; Handbooks; Electronic books; Handbooks and manuals